Reliability of low-cost colorimetric phosphate and nitrate tests used by citizen scientists to assess river water quality - von Benzon, Elena; Bagshaw, Elizabeth A.; Perkins, Rupert; Browning, Simon; Tibbits, Thomas N. D. (Frontiers in Environmental Science, 2025)
Water quality in United Kingdom rivers is an issue of increasing public and political concern, yet statutory water quality monitoring programmes are resource limited. Whilst citizen scientists can gather large quantities of data, the quality of these data is not well understood, particularly the accuracy and bias of data reported by volunteers using low-cost colorimetric nutrient tests. In this study, the performance of popular, low-cost field tests used to assess phosphate and nitrate concentrations in freshwater were compared to accredited laboratory methods by paired sample analysis. During three mass sampling events in the River Wye catchment, some tests demonstrated a good degree of accuracy when performed by volunteers: 62% of Hanna Phosphate Checker results and 66% of Hach nitrate test strip results were in agreement with paired laboratory results. In comparison, La Motte Insta-test strips for phosphate, widely used by citizen scientists across the United Kingdom, demonstrated poor performance in this study: only 17% of phosphate results reported by volunteers were in agreement with laboratory analysis of paired samples, although we note their utility for identifying high concentration events. We conclude that a comprehensive assessment of any low-cost test kit being considered for use by volunteer monitoring programmes is a critical first step to producing relevant, high-quality and trustworthy citizen science water quality datasets that can reliably help fill monitoring data gaps. Nevertheless, our results demonstrate that, with appropriate low-cost test kits and the correct training, volunteers can produce high-quality datasets that enhance understanding of water quality issues across river catchments and could reliably support statutory monitoring.